Help Seeking Attitudes and Willingness to Seek Psychological Help: Application of the Theory of Planed Behavior - Wijerathnage Chandrasekara (International Journal of Management, Accounting and Economics, 2016)
Though there is a high level of mental health related difficulties among university students, only one third of them seek psychological help despite the evidence-based treatments for mental health problems. Therefore, this paper examines the help seeking attitudes towards psychological help services and willingness to seek psychological help based on the Theory of Planned Behavior (TPB). Attitudes, subjective norms, and behavioral control were measured using the Inventory of Attitudes toward Seeking Mental Health Services (IASMHS). Barriers for seeking psychological help were measured using Mental Health Service Utilization Questions (MHSUQ) whereas intention to seek psychological help was measured using the General Help Seeking Questionnaire – Vignette Version (GHSQ-V). 600 students were interviewed from three Sri Lankan state universities from January 2015 to March 2015. Results suggested that positive attitudes towards psychological help service positively associate with greater willingness to seek psychological help. Further, female students show a greater attitude seeking psychological help than male students. The most common barrier reported by students was that the fear of what relatives, friends might think. In contrast, students who follow psychology as a subject have a significantly higher level of positive attitude towards seeking psychological help than the students who do not follow. Findings suggest that mental health campaigns are required to focus their attention to change the negative attitudes towards mental health services among university students. Further, it highlights the importance of changing the public attitudes towards mental illnesses.